Literary Magic in The BFG: Crafting a Timeless Tale of Children Literature - Nuzulia, Rahma (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2024)
ABSTRACT ENGLISHThe purpose of this study is to investigate the literary strategies that Roald Dahl utilized in his novel